2023
DOI: 10.1590/1807-1929/agriambi.v27n1p42-50
|View full text |Cite
|
Sign up to set email alerts
|

Potassium fertilization in the cultivation of sour passion fruit under irrigation strategies with brackish water

Abstract: In the Brazilian semiarid region, the occurrence of water sources with high salt concentrations stands out as a limiting factor for the production of most crops under irrigated conditions. This research was conducted to evaluate the physical and chemical quality of sour passion fruit as a function of brackish water irrigation strategies and potassium doses. The experiment was carried out under field conditions using a randomized block design in a 6 × 2 factorial scheme, consisting of six strategies of irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Vale destacar que as plantas também possuem a capacidade de se aclimatar, até certo ponto as condições de estresse por meio de processos fisiológicos comuns em plantas glicófitas, como o efeito do ajustamento osmótico. Pinheiro et al (2023) avaliando a adubação potássica (60 e 100% da recomendação de K2O) e diferentes estratégias de manejo no uso de águas salinas (1,3 e 4,0 dS m -1 ), também observaram redução nos parâmetros morfológicos dos frutos de maracujazeiroazedo quando as plantas foram irrigadas com água de 4,0 dS m -1 durante todo o ciclo de cultivo, na fase vegetativa assim como também na fase de floração. O aumento na condutividade elétrica da água de irrigação reduziu o diâmetro equatorial (DE) dos frutos de maracujazeiroazedo 'BRS Rubi do Cerrado' independente da aplicação foliar do peróxido de hidrogênio.…”
Section: Resultsunclassified
“…Vale destacar que as plantas também possuem a capacidade de se aclimatar, até certo ponto as condições de estresse por meio de processos fisiológicos comuns em plantas glicófitas, como o efeito do ajustamento osmótico. Pinheiro et al (2023) avaliando a adubação potássica (60 e 100% da recomendação de K2O) e diferentes estratégias de manejo no uso de águas salinas (1,3 e 4,0 dS m -1 ), também observaram redução nos parâmetros morfológicos dos frutos de maracujazeiroazedo quando as plantas foram irrigadas com água de 4,0 dS m -1 durante todo o ciclo de cultivo, na fase vegetativa assim como também na fase de floração. O aumento na condutividade elétrica da água de irrigação reduziu o diâmetro equatorial (DE) dos frutos de maracujazeiroazedo 'BRS Rubi do Cerrado' independente da aplicação foliar do peróxido de hidrogênio.…”
Section: Resultsunclassified
“…The excess of salts in irrigation water also induces the inhibition of physiological and metabolic processes, negatively affecting the production components [68]. Reductions in the production components of sour passion fruits as a function of irrigation water salinity have also been reported in studies conducted by [13,15,39].…”
Section: Discussionmentioning
confidence: 92%
“…Two studies have indicated that the sensitivity and tolerance of crops to salt stress may vary between species and cultivars of the same species, in addition to depending on climatic conditions, type of soil, plant development stage, irrigation method, and time of exposure to salt stress [ 16 , 39 ]. In the present study, it was observed that the deleterious effects of salinity were intensified in the second cycle, possibly due to a longer period of exposure to salt stress and the accumulation of salts in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the potential of cashew production in the Northeast region, the irregularity and poor distribution of rainfall in the region, associated with high temperatures, results in high evapotranspiration rates, complicating the cultivation of this crop [5]. In this scenario, the employment of irrigation emerges as a viable solution for continuous cultivation, allowing the expansion of productive regions over the year [6].…”
Section: Introductionmentioning
confidence: 99%